Targeting WNT Signaling for Multifaceted Glioblastoma Therapy - McCord, Matthew; Mukouyama, Yoh-suke; Gilbert, Mark R.; Jackson, Sadhana (Frontiers in Cellular Neuroscience, 2017)
The WNT signaling pathway has been of great interest to developmental biologists for decades and has more recently become a central topic for study in cancer biology. It is vital for cell growth and regulation of embryogenesis in many organ systems, particularly the CNS and its associated vasculature. We summarize the role of WNT in CNS development and describe how WNT signaling makes key contributions to malignant glioma stemness, invasiveness, therapeutic resistance, and angiogenesis. The role of WNT in these mechanisms, along with creation and maintainance of the blood-brain barrier (BBB), points to the potential of WNT as a multi-faceted target in malignant glioma therapy.